Analisis Kesalahan Penggunaan Bahasa Indonesia Siswa Kelas VII dalam Menulis Teks Deskripsi di Sekolah Menengah Pertama Negeri 1 Binjai - Arezsya, Rahma Andien; Helmi, Muthia Ayyuni; Daulay, Muhammad Anggie Januarsyah; Billa, Salma Nursyah; Andini, Resti (Jurnal Bahastra, 2025)
This study aims to analyze errors in the use of standard Indonesian language in descriptive texts written by seventh-grade students at State Junior High School 1 Binjai. The research employed a descriptive qualitative method, with data collected through comprehensive reading and systematic note-taking of students’ descriptive texts. The sample consisted of three texts analyzed across four linguistic aspects. The findings reveal four primary categories of errors: (1) capitalization errors, particularly in sentence openings, days of the week, and honorifics; (2) lexical errors, including the use of non-standard words and incorrect possessive pronouns; (3) punctuation errors, mainly involving the misuse of commas in compound sentences and periods at the end of sentences; and (4) sentence construction errors, encompassing problems of unity, coherence, and conciseness. These results highlight the necessity of strengthening instruction in standard Indonesian to enhance students’ writing skills, particularly in spelling, word choice, punctuation, and sentence structure. The study underscores the critical role of accurate language use in developing students’ communicative competence and lays the groundwork for further pedagogical interventions aimed at improving language accuracy in secondary education.